2013
DOI: 10.3109/13880209.2012.762405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ethnomedicinal combination containingSemecarpus kurziiandHernandia peltataused for the management of inflammation

Abstract: The SKL and HPB extract, alone (500 mg/kg) and in combination, (250 mg/kg each) had significant analgesic and antiinflammatory activity, probably by inhibiting the release of certain inflammatory mediators and membrane stabilization, due to the presence of triterpenes, tannins and related phytochemicals in the extracts. Thus, our results demonstrated that this combination provide the scientific rationale of its folk use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…The ability of ASE to reduce the inflammation induced by carrageenan was possibly due to some phytochemicals that may block the release of any of those mediators. On the other hand, dextran-mediated inflammation was reduced probably as a result of antihistaminic effects of the extract, as dextran can cause inflammation through both histamine and serotonin (Das et al, 2013). The ability of ASE to reduce the oedema volume produced by carrageenan, dextran and histamine suggests that the phytochemicals present in the extract may block the release of any of those mediators, alone or in combination.…”
Section: Discussionmentioning
confidence: 94%
“…The ability of ASE to reduce the inflammation induced by carrageenan was possibly due to some phytochemicals that may block the release of any of those mediators. On the other hand, dextran-mediated inflammation was reduced probably as a result of antihistaminic effects of the extract, as dextran can cause inflammation through both histamine and serotonin (Das et al, 2013). The ability of ASE to reduce the oedema volume produced by carrageenan, dextran and histamine suggests that the phytochemicals present in the extract may block the release of any of those mediators, alone or in combination.…”
Section: Discussionmentioning
confidence: 94%
“…Zones of inhibition ranged between 10 and 28 mm at 10% concentration of extract while minimum inhibitory concentration between 0.5% and 2% against tested micro‐organisms. Antiinflammatory activity of extract was assessed by human red blood cell membrane stabilization method in vitro (Das et al ., ), and results showed that a minimum of 50 µg/mL concentration of E. officinalis extract is required to show antiinflammatory effect. Based upon these findings, 10% concentration of E. officinalis extract was finalizedx for subgingival gel application in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Secara tradisional, kulit batang, dahan, dan daunnya digunakan untuk pengobatan malaria, demam, keracunan, dan pereda rasa sakit (Dittmar 1991;Lakshmi et al 2009;Arini & Kinho 2015). Penelitian terkini juga mengungkap berbagai jenis senyawa kimia dari bagian-bagian tumbuhannya yang berpotensi sebagai obat kanker dan tumor (Suthiwong et al 2018;Aimaiti et al 2019), pereda nyeri dan mengurangi peradangan (Das et al 2013;Wei et al 2018). Jenis ini juga memiliki kandungan lemak pada bagian biji yang berpotensi sebagai bahan baku campuran biodiesel (Duyfjes 1996), namun hingga kini belum ada penelitian yang membuktikannya.…”
Section: Pendahuluanunclassified